2001
DOI: 10.1074/jbc.m108903200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Characterization of theMycobacterium tuberculosis β-Ketoacyl-acyl Carrier Protein Synthases KasA and KasB

Abstract: Mycolic acids are vital components of the Mycobacterium tuberculosis cell wall, and enzymes involved in their formation represent attractive targets for the discovery of novel anti-tuberculosis agents. Biosynthesis of the fatty acyl chains of mycolic acids involves two fatty acid synthetic systems, the multifunctional polypeptide fatty acid synthase I (FASI), which performs de novo fatty acid synthesis, and the dissociated FASII system, which consists of monofunctional enzymes, and acyl carrier protein (ACP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
134
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 43 publications
(43 reference statements)
5
134
0
Order By: Relevance
“…The FAS II complex in M. tuberculosis is located in a genetic locus that also contains a lone, uncharacterized acyl-CoA carboxylase carboxyltransferase subunit, accD6 (␤ 6 ) (6), which could provide malonylCoA to the ␤-ketoacyl-ACP synthases and to FAS I. MalonylCoA is converted to malonyl-ACP by the malonyl-CoA-ACP transacylase (FabD) (19) and is utilized by the ␤-ketoacyl-ACP synthases (KasA/KasB) (5,18,27) in successive reactions with the other enzymes of the FAS II complex to produce the meromycolic acids. Protein-protein interaction analyses have shown that FabD is a structural component of the FAS II complex (30) and that KasA, KasB, InhA, MabA (FabG1), and FabH (␤-ketoacyl-ACP synthase III) interact with each other (31).…”
Section: Discussionmentioning
confidence: 99%
“…The FAS II complex in M. tuberculosis is located in a genetic locus that also contains a lone, uncharacterized acyl-CoA carboxylase carboxyltransferase subunit, accD6 (␤ 6 ) (6), which could provide malonylCoA to the ␤-ketoacyl-ACP synthases and to FAS I. MalonylCoA is converted to malonyl-ACP by the malonyl-CoA-ACP transacylase (FabD) (19) and is utilized by the ␤-ketoacyl-ACP synthases (KasA/KasB) (5,18,27) in successive reactions with the other enzymes of the FAS II complex to produce the meromycolic acids. Protein-protein interaction analyses have shown that FabD is a structural component of the FAS II complex (30) and that KasA, KasB, InhA, MabA (FabG1), and FabH (␤-ketoacyl-ACP synthase III) interact with each other (31).…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated protein b-ketoacyl-ACP synthase (KasB, Rv2246) is, together with KasA, involved in the synthesis of mycolic acids (Schaeffer et al, 2001). KasA has been shown to specifically elongate palmitoyl-CoA to monounsaturated fatty acids averaging 40 carbons in length and overproduction of KasB in the presence of KasA leads to the production of even longer chains.…”
Section: Cell Wallmentioning
confidence: 99%
“…CER is a drug that is produced naturally by Cephalosporium caerulens and exhibits potent activity against a wide variety of yeast, fungi, and bacteria (53) through inhibition of both FAS-I and FAS-II (43,54). Several studies (34,43,55,56) have demonstrated that it specifically targets ␤-ketoacyl-ACP synthases by covalently attaching to the active site cysteine. CER is known to inhibit KasA activity in vitro (34,56).…”
Section: Induction Of the Kasa-containing Complex By Inha-inhibitory mentioning
confidence: 99%
“…Several studies (34,43,55,56) have demonstrated that it specifically targets ␤-ketoacyl-ACP synthases by covalently attaching to the active site cysteine. CER is known to inhibit KasA activity in vitro (34,56). However, this drug was not able to inhibit InhA activity in vitro (Table IV), and the MIC of CER for a strain overproducing InhA was found to be comparable with that for the control strain (Table III), confirming that InhA is not inhibited by CER.…”
Section: Induction Of the Kasa-containing Complex By Inha-inhibitory mentioning
confidence: 99%
See 1 more Smart Citation